2020
DOI: 10.1371/journal.pone.0243028
|View full text |Cite
|
Sign up to set email alerts
|

The effect of area deprivation on COVID-19 risk in Louisiana

Abstract: Background Louisiana in the summer of 2020 had the highest per capita case count for COVID-19 in the United States and COVID-19 deaths disproportionately affects the African American population. Neighborhood deprivation has been observed to be associated with poorer health outcomes. The purpose of this study was to examine the relationship between neighborhood deprivation and COVID-19 in Louisiana. Methods The Area Deprivation Index (ADI) was calculated and used to classify neighborhood deprivation at the ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 42 publications
(53 reference statements)
4
41
0
1
Order By: Relevance
“…A second important risk factor in this study was the relative presence of home for rent in a census section. In our opinion, and as reported by others [13], this could be an indirect socioeconomic deprivation indicator quantifying the magnitude of geographically determined social inequalities in health. For this reason, it should be interpretated according to two other variables that have a similar meaning as residents with university degree and residents with secondary level education.…”
Section: Discussionsupporting
confidence: 72%
“…A second important risk factor in this study was the relative presence of home for rent in a census section. In our opinion, and as reported by others [13], this could be an indirect socioeconomic deprivation indicator quantifying the magnitude of geographically determined social inequalities in health. For this reason, it should be interpretated according to two other variables that have a similar meaning as residents with university degree and residents with secondary level education.…”
Section: Discussionsupporting
confidence: 72%
“…This social determinant may similarly play a role in higher AI/AN COVID-19 infections in non-CHSDA counties, as urban Indians are also more likely to live in households that lack plumbing facilities [ 26 ]. Living in lower SES communities is associated with worse health, including higher risk of COVID-19 [ 44 ]. The COVID-19 infection disparity for AI/ANs may be explained in part by the fact that AI/ANs, both living on reservations or in urban areas, tend to live in more impoverished neighborhoods than White-nHs [ 26 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 158 counties in 10 U.S. metropolitan areas with early COVID-19 surges, the higher the proportion of the non-White population, the higher the incidence and mortality from COVID-19-a gradient that was steeper in poorer Environmental Health Perspectives 075001-2 129(7) July 2021 counties (Adhikari et al 2020). A census tract-level study in Louisiana found that people in the most deprived neighborhoods had a nearly 40% higher risk of contracting COVID-19 than those in the least deprived neighborhoods (KC et al 2020). Similar results emerged in studies in numerous locations (Andersen et al 2021;Bilal et al 2021;Das et al 2021;De Ridder et al 2021;Emeruwa et al 2020;Hu et al 2021a;Lewis et al 2020;Nguyen et al 2020;Scannell Bryan et al 2021).…”
Section: Poverty and Racismmentioning
confidence: 99%